(untitled) (Ágora de Heterodoxias, 2025)
The SDG Agenda created in 2015 integrates 17 objectives that must be met by its signatories by 2030. Its roots go back to the establishment of Agenda 21 at the Rio de Janeiro Summit in 1992 and are derived from the renewed Development Goals Millennium Development Goals defined in the year 2000. In formal terms, the SDGs have generated more acceptance than rejection, although they have been the subject of various criticisms regarding their vision, their contents and their degree of compliance. Beyond the technical adjustments that may be suggested for its full execution, a thorough review of its conceptual bases is proposed with a view to its reformulation and alternative overcoming.